Energy Efficient Relay Positioning and Power Allocation for One-Way N-Relay Channel - 周健 朱灿焰 王东林 季爱明 (东华大学学报（英文版）, 2016)
Two end-users which have symmetric traffic requirements in terms of data rate are considered. They exchange information in Rayleigh flat-fading channels and multiple serial half-duplex relay nodes are employed to extend the communication coverage and assist the bidirectional communication between them using the analog network coding（ ANC） protocol. With the objective of minimizing the sum transmit energy at the required data rate c,the optimal relay positioning and power allocation problem is firstly investigated and then the sub-optimal solutions for a two-relay channel are proposed,due to no close-form optimal solution. Furthermore,a sub-optimal scheme of relay positioning and power allocation,called equal-distance equal-transmit-power（ EDEP） for an arbitrary Nrelay channel,N 〉 1 is proposed. Simulation results demonstrate a consistence with our proposed scheme.